First report of Aedes albopictus in the state of Santa Catarina, Brazil - Löwenberg-Neto, Peter (2002)
Three adult females of Aedes (Stegomyia) albopictus (Skuse) were captured using a human bait in the surrounding dwelling area of the remaining rain forest in Itaguassu beach, island of São Francisco do Sul, northern coast of the state of Santa Catarina, Brazil.